Paul Maenz Jahresbericht 1978. - Celant, Germano; Paul Maenz, Köln (Köln : Paul Maenz, 1979)
Penone, Giuseppe ; De Maria, Nicola ; Bartolini, Luciano ; Tatafiore, Ernesto ; Clemente, Francesco ; Fabro, Luciano ; Boetti, Alighiero ; Paladino, Mimmo ; Garutti, Alberto ; Longobardi, Nino ; Anselmo, Giovanni ; Salvo ; Mariani, Carlo Maria ; Chia, Sandro ; Paolini, Giulio ; Icaro, Paolo ; Kounellis, Jannis
Duits
boek